A study on factors influencing employees satisfaction / Aly Unajieha Mohd Tamami - Mohd Tamami, Aly Unajieha (Faculty of Business and Management, 2014)
Employee job satisfaction can become problem if the organization become more focused on production and revenues, rather than their own employees who work and help the organization become more productivity. It is hard to determine their employee job satisfaction because every employee has different perception when they work in the organization. If the employee feels that the organization not fulfil their needs as an employee in that organization, they feel dissatisfaction and feels they are not part of the company. In this situation, the employee may have intention to leave the company. The purpose on this study is to examine the relationship between superiors, work environment and workload .The data has been collected from employees at New Hoong Fatt Company by distributing survey to 80 employees that being selected randomly. This study also discussed some recommendations to solve this problem.